PENGUATAN MASYARAKAT LITERASI MELALUI KOMUNITAS LITERASI “KARSA” DENGAN PENDEKATAN COMMUNITY BASED PARTICIPATORY RESEARCH (CBPR) - Ahmad Fauzi; Nurlita Nindya Putri; Alfiarany Choirun Nisa; Alissa Qotrunnada Rohmah; Febrina Zakiya Daroja; Heeba Alya Ronan; Irma Setya Ningsih; Miftahul Ainiyah; Vina Afrina Fitri; Shifa Shalsabila (As-Sidanah, 2023)
The low interest in reading is still a serious problem faced by the Indonesian government. One of them occurred in Kandangan Village, Senduro District, Lumajang Regency. This was due to the lack of public awareness about the importance of literacy culture, lack of interest in learning, and limited facilities and infrastructure that supported reading activities. So that researchers were interested in studying reading interest through the formation of a literacy community. This study aims to describe the community as an intermediary medium for strengthening public interest in reading through the Community Service Program research program. The method used in this research was CBPR (Community Based Participatory Research) by involving the community in program implementation as partners. The result of this research was the formation of a literacy community which is intended as an intermediary media to increase public literacy, with this it is highly expected for the advancement of literacy, especially at SMPN 2 Senduro. Community strengthening was carried out through several actions, including FGD (Focus Groups Discussion), literacy socialization, establishment of reading house and KARSA literacy community. With this, it can make the sustainability of literacy culture in Kandangan Village.